Analisis Dampak Inflasi dan Nilai Tukar terhadap Indeks Saham Syariah Indonesia (JJII-70) Sebelum dan Sesudah Pemilu 2024 - Mujahid, Muhammad Fathan; Junaedi, Dedi; Salistia, Faisal (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study analyzes the impact of inflation and exchange rates on the Indonesia Sharia Stock Index (JJII-70) before and after the 2024 Election. Using daily time series data and t-tests, the results show that inflation had a significant negative effect on JJII-70 before the election, but no significant effect afterward. The exchange rate had a significant negative effect in both periods, with a stronger impact after the election. These findings indicate that the 2024 Election influenced JJII-70’s sensitivity to macroeconomic variables and reflect increased investor confidence and greater stability in the sharia stock market post-election. Keywords: Inflation, Exchange Rate, Indonesia Sharia Stock Index (JJII-70), 2024 Election, Sharia Stock Market.